MAKNA IJAZ DALAM AL-QUR'AN JUZ 28,29 DAN 30 ( KAJIAN BALAGHAH) - Azkia, Putri Farhatul; Nugrahawan, Ahmad Rizki (Hijai - Journal on Arabic Language and Literature, 2024)
A broader meaning. Researchers will discuss the meaning of ijaz and its classification related to the verses of the Quran, especially in chapters twenty eight, twenty nine and thirty, in order to understand the meaning contained in the verses of those chapters, and can be used as a reference for subsequent learning. This type of research uses qualitative descriptive analysis. The study will describe and group the results found in the data sources. The method used by the researcher is content analysis, as the discussion is in-depth and deductive, the researcher reads the text deeply and carefully to obtain the intended content in the research. In this study, the researcher found ijaz in chapters twenty eight, twenty nine and thirty.